2001
DOI: 10.1186/1471-2407-1-17
|View full text |Cite
|
Sign up to set email alerts
|

COL11A1 in FAP polyps and in sporadic colorectal tumors

Abstract: Background : We previously reported that the α-1 chain of type 11 collagen (COL11A1), not normally expressed in the colon, was up-regulated in stromal fibroblasts in most sporadic colorectal carcinomas. Patients with germline mutations in the APC gene show, besides colonic polyposis, symptoms of stromal fibroblast involvement, which could be related to COL11A1 expression. Most colorectal carcinomas are suggested to be a result of an activated Wnt-pathway, most often involving an inactivation of the APC gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 17 publications
(22 reference statements)
3
44
0
1
Order By: Relevance
“…2). These data are consistent with a study which found a correlation between Col11a1 expression in colorectal carcinoma and an activated β-catenin-Lef1/Tcf pathway (Fischer et al, 2001). Analysis of the Col11a1 promoter identified at least six potential Lef1 binding sites, but only two were found to bind Lef1 in vitro (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…2). These data are consistent with a study which found a correlation between Col11a1 expression in colorectal carcinoma and an activated β-catenin-Lef1/Tcf pathway (Fischer et al, 2001). Analysis of the Col11a1 promoter identified at least six potential Lef1 binding sites, but only two were found to bind Lef1 in vitro (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Intense 125 I-ET-1 binding once again correlated with both fibroblast and endothelial cell staining. Collagen type XI (Col XI), which was used to further define tumor stroma, was only present in tumor sections and not normal tissue, confirming previous reports of its association with colorectal pathology (20,21).…”
Section: Efficacy Of Zibotentan In In Vitro Models Of Colorectal Cancersupporting
confidence: 59%
“…Genes associated with Wnt/β-catenin signalling pathway: Both CDH11 and COL11A1 are associated with the Wnt/β-catenin signalling pathway [54,55,56]. We have found that treatment of PC3 cells with Ganoderma ethanol-based extracts caused a significant increase in the expression of CDH11.…”
Section: Genes Associated With Cell Cycle Controlmentioning
confidence: 89%